Memories Of The Creativity: A Visual Criticism Of The Evolution Of Creativity In The Era Of Artificial Intelligence: Memories Of The Creativity: A Visual Criticism Of The Evolution Of Creativity In The Era Of Artificial Intelligence - Ahmad Naswin; I Putu Adi Saskara; I Putu Adi Pratama (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Alit Kumala Dewi's